Seasonal availability calendars show the importance of vegetables during the challenging lean seasons in Africa - Kauppila, Saija E.; Vansant, Emilie C.; Kennedy, Gina; Termote, Celine; Den Braber, Bowy; Hall, Charlotte; Nabuuma, Deborah; Owori, Moses; Vang Rasmussen, Laura (2025)
Seasonal patterns of food availability, meaning the wide array of species that are abundant during specific months of a year in a given place, are at the heart of food systems and celebrated worldwide (e.g., mushroom season, strawberry season, oyster season). We know that dietary diversity, or consumption of a wide variety of foods within and across food groups is a central tenant for a healthy diet – and dietary diversity can be boosted by consumption of seasonal foods. The concept of balance or proportionality of foods on the plate is another central tenant of a healthy diet. Yet, eating a balanced and seasonally appropriate diet is often overshadowed in food security policies and interventions by a focus on staple and animal source foods. This brief describes the results from participatory explorations of seasonal food availability in different countries in Africa.